Regulation of ECP fimbriae‐related genes by the transcriptional regulator RcsAB in Klebsiella pneumoniae NTUH‐K2044. (8th February 2022) - Shen, Lifei; Zhang, Jiaxue; Xue, Jian; Du, Ling; Yuan, Lingyue; Nie, Hao; Dai, Sue; Yu, Qian; Li, Yingli
Abstract: Klebsiella pneumoniae is one of the major pathogens causing nosocomial infections. The regulator of capsule synthesis (Rcs) system is a complex signal transduction pathway that is involved in the regulation of virulence factors of K. pneumoniae as an important transcriptional regulator. The RcsAB box‐like sequence was found to be present in the promoter‐proximal regions of ykgK, one of the ECP fimbriae‐related genes, which suggested the expression of ECP fimbriae may be regulated by RcsAB. The ykgK gene in K. pneumoniae has 86% similarity to the ecpR gene in Escherichia coli . Nucleotide sequence alignment revealed a similar ECP fimbriae gene cluster including six genes in K. pneumoniae, which was proved to be on the same operon in this study. The electrophoretic mobility shift assay and DNase I assay, relative fluorescence expression, β‐galactosidase activity, and relative gene expression of ykgK in the wild‐type and mutant strains were performed to determine the transcriptional regulation mechanism of RcsAB on ECP fimbriae. The mutant Δ ykgK and complementary strain Δ ykgK /cΔ ykgK were constructed to complete the Galleria mellonella larvae infection experiment and biofilm formation assay. This study showed that RcsAB binds directly to the promoter region of the ykgK gene to positively regulate ECP fimbriae‐related gene clusters, and then positively affect the biofilm formation.